THE MOST USED PROGRAMS FOR CREATING MOBILE APPLICATIONS (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2023)
This article provides an overview of the most widely used software tools for creating mobile applications. It covers popular integrated development environments (IDEs), frameworks, and platforms that enable developers to build mobile apps for different operating systems. The article discusses tools such as Android Studio, Xcode, React Native, Flutter, Xamarin, Ionic, and PhoneGap (Apache Cordova), highlighting their features, capabilities, and target platforms. It also briefly mentions additional tools and resources commonly used in mobile app development. The information presented aims to assist developers in choosing the right software for their mobile app projects.